Successful field performance in warm and dry environments of soybean expressing the sunflower transcription factor HB4 - Ribichich, Karina Fabiana (2020)
Fil: Ribichich, Karina Fabiana. Universidad Nacional del Litoral. Facultad de Bioquímica y Ciencias Biológicas. Instituto de Agrobiotecnología del Litoral Santa Fe, Argentina.